The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1089/aid.2009.0038
|View full text |Cite
|
Sign up to set email alerts
|

Elevated NT-pro-BNP Levels Are Associated with Comorbidities among HIV-Infected Women

Abstract: HIV infection is associated with left ventricular (LV) dysfunction and accelerated atherosclerosis. These conditions result in elevation of plasma natriuretic peptide (NP) levels. The present study compares N-terminal-pro-BNP (NT-pro-BNP) levels in HIV-infected and -uninfected women and identifies factors influencing NT-pro-BNP levels in HIV-infected women. A total of 454 HIV-infected and 200 HIV-uninfected participants from the Women’s Interagency HIV Study (WIHS) had NT-pro-BNP determination. Elevated NT-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Elevated NT-proBNP levels are associated with comorbidities that include chronic renal failure, type 2 diabetes, anemia, and acute coronary syndrome [28,29]. In this study, the most frequent comorbidity was diabetes, and patients in the Low group (NT-proBNP < 380 mg/mL) were less likely to have comorbidities compared with the patients in the High group.…”
Section: Discussionmentioning
confidence: 54%
“…Elevated NT-proBNP levels are associated with comorbidities that include chronic renal failure, type 2 diabetes, anemia, and acute coronary syndrome [28,29]. In this study, the most frequent comorbidity was diabetes, and patients in the Low group (NT-proBNP < 380 mg/mL) were less likely to have comorbidities compared with the patients in the High group.…”
Section: Discussionmentioning
confidence: 54%
“…In the study by Mansoor [16], NTproBNP levels in the general population were found to be associated with the presence of anaemia and renal dysfunction. In the case of women infected with HIV, no relation with the use of HAART was found.…”
Section: Discussionmentioning
confidence: 93%
“…The patients were part of a previous research series [16] created to study the left ventricular mass in patients with HIV infection. The patients in this serie who were aged over 40 years were invited to cooperate in the present study, to determine levels of NT-proBNP in peripheral blood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from a very early study, it is shown that despite restoration to the normovolemia, BNP levels were not reduced to their normal levels [38]. Other studies showed that, aside cardiovascular conditions, BNP levels can also be affected by some neurologic conditions like hemorrhagic stroke [39] and ischemic stroke [40], by critical illnesses like sepsis [41,42] and HIV [43], by some pulmonary diseases like pulmonary hypertension [44,45] and pulmonary embolism [46,47]; or by some other conditions like anemia [48,49], cirrhosis [50], and hypertension [51]. Moreover, in hemodialysis patients, the levels of natriuretic peptides also seem to be related to the dialytic membranes.…”
Section: Limitationsmentioning
confidence: 99%